2021
DOI: 10.1073/pnas.2105968118
|View full text |Cite
|
Sign up to set email alerts
|

Reverse-transcribed SARS-CoV-2 RNA can integrate into the genome of cultured human cells and can be expressed in patient-derived tissues

Abstract: Prolonged detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA and recurrence of PCR-positive tests have been widely reported in patients after recovery from COVID-19, but some of these patients do not appear to shed infectious virus. We investigated the possibility that SARS-CoV-2 RNAs can be reverse-transcribed and integrated into the DNA of human cells in culture and that transcription of the integrated sequences might account for some of the positive PCR tests seen in patients. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
268
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(283 citation statements)
references
References 75 publications
(110 reference statements)
12
268
1
2
Order By: Relevance
“…However, one recent study revealed that SARS-CoV-2 infection induced retrotransposon activation, leading to the formation of chimeric virus-retrotransposon RNA (Yin et al, 2021 ). Zhang et al also observed the host genome integration of SARS-CoV-2 under overexpressing LINE1 in cultured human cells (Zhang et al, 2021 ). These reports indicate a likely chance of SARS-CoV-2 integration into host genome (Yin et al, 2021 ; Zhang et al, 2021 ), which have fueled concerns about its potential long-term health threat in the infected individuals.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…However, one recent study revealed that SARS-CoV-2 infection induced retrotransposon activation, leading to the formation of chimeric virus-retrotransposon RNA (Yin et al, 2021 ). Zhang et al also observed the host genome integration of SARS-CoV-2 under overexpressing LINE1 in cultured human cells (Zhang et al, 2021 ). These reports indicate a likely chance of SARS-CoV-2 integration into host genome (Yin et al, 2021 ; Zhang et al, 2021 ), which have fueled concerns about its potential long-term health threat in the infected individuals.…”
mentioning
confidence: 98%
“…Zhang et al also observed the host genome integration of SARS-CoV-2 under overexpressing LINE1 in cultured human cells (Zhang et al, 2021 ). These reports indicate a likely chance of SARS-CoV-2 integration into host genome (Yin et al, 2021 ; Zhang et al, 2021 ), which have fueled concerns about its potential long-term health threat in the infected individuals. Thus, more evidences are explicitly required to address this issue.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Prolonged viral RNA shedding may induce clonal expansion of NK cells in an antigen-specific manner, similar to the response to cytomegalovirus infection to acquiring memory features (38). Since reverse-transcribed SARS-CoV-2 RNA can integrate into the genome of cultured human cells and can be expressed in patient-derived tissues (39), there might also be latent SARSCoV-2 virus in the reservoir cells in PPSs that could lead to the prolonged expansion of NK cells. Although our study confirms some findings and provides new data on the innate and adaptive immune landscape of patients with PS who have recovered from COVID-19 one year after discharge, we recognize limitations that might be overcome with larger sample sizes and matched control populations.…”
Section: The Interrelation Of Immune Cells and Its Association With Clinical Features In Covid-19mentioning
confidence: 99%
“…Their data suggests that virion and subgenomic RNAs are stable in cellular doublemembrane vesicles and, therefore, can be detected long after the acute infection 22 . Furthermore, Zhang et al (2021) found that parts of the reverse-transcribed SARS-CoV-2 RNA can integrate into the human genome without the ability to yield infectious viruses and suggest that this could explain at least partly the long term RNA shedding 23 .…”
Section: Introductionmentioning
confidence: 99%